ElasticSearch cookbook : over 120 advanced recipes to search, analyze, deploy, manage, and monitor data effectively with ElasticSearch /: over 120 advanced recipes to search, analyze, deploy, manage, and monitor data effectively with ElasticSearch. (2013) - Unknown
No abstract available